Failure Mechanism Analysis and prevention of Silver Electrode Corrosion. (November 2020) - Zhang, Lei; Jiang, Baihong; Jiao, Dacheng; Yuan, Tao; Peng, Guangrui; Wu, Xian
Abstract: In this paper, the failure mechanism of sulfide corrosion of a batch of silver electrodes was studied by means of environmental simulation test, scanning electron microscopy (SEM), energy spectrum analysis (EDS), micro-CT, infrared spectroscopy analyzer(FTIR), pyrolysis gas chromatography mass spectrometry (Py-GC-MS) and specific surface area (BET) analysis. The results showed that the H2 S in the air entered the silver electrode surface through the rubber by the adsorption and permeation effects, and corroded the silver electrode. What's more, The change of pore size in silicone rubber will affect the H2 S corrosion reaction. The smaller the pore, the higher the specific surface area and the more polar H2 S molecules adsorbed by rubber. So the special pore distribution of the size of the intercalation was beneficial to reduce the diffusion resistance of H2 S molecules in rubber. The above analysis results also provided ideas and direction for the improvement of silicone rubber. The pore distribution of silicone rubber could be controlled by controlling the viscosity and the surface drying time of the glue solution, so as to ensure the filling effect of the silicone rubber and prevent the corrosion failure of the silver electrode.